Peristilahan dalam Mutong (Aktivitas Menyadap Karet Tradisional) pada Masyarakat Dayak Ketungau Sesat: Kajian Etnolinguistik - Pabianus Simon (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research focuses on the terminology in mutong (traditional rubber tapping activity) in the Dayak Ketungau Sesat community. The mutong activity in question is still carried out traditionally both in terms of tools and processes carried out. The method used in this research is descriptive. The data in this study are terms found in mutong activities in the Dayak Ketungau Sesat community. In this study, researchers focus on describing and culturally interpreting the terms in mutong activities (rubber tapping) traditionally by the Dayak Ketungau Sesat community. Based on the results of the research conducted, researchers managed to collect 51 terms consisting of 7 classifications. The data are based on tool classification as many as 10, based on part name classification as many as 3, based on process classification as many as 16, based on method classification as many as 4, based on properties as many as 11, based on place names as many as 4, and based on results as many as 3 terms. The researcher also succeeded in describing the cultural meaning of terminology in mutong activities in the Dayak Ketungau Sesat community, which amounted to 51 terms based on tool classification, part names, processes, methods, characteristics, place names, and based on results